2017
DOI: 10.21037/tlcr.2017.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Correlation in histological subtypes with high resolution computed tomography signatures of early stage lung adenocarcinoma

Abstract: Background: Uncertainty remains on the association between image characteristics of the nodules in computed tomography (CT) scans and lung adenocarcinoma histopathologic subtypes. We aimed to estimate the correlation between preoperative high resolution computed tomography (HRCT) scan and postoperative histopathology of stage IA lung adenocarcinoma in East Asian Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Moreover, our study involved more patients with mutations in EGFR, BRAF, and ERBB2, further supporting the fact that EGFR was the most frequently mutated cancer gene in MIA, AIS, and IAC (9). Our founding also indicated that there was a high discrepancy of driver mutations in NSCLC patients with ground-glass nodules (GGNs) (4,38). EGFR mutation status including L858R mutation and 19 deletions, KRAS mutations or ALK rearrangements occurred frequently in patients with GGO (34).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, our study involved more patients with mutations in EGFR, BRAF, and ERBB2, further supporting the fact that EGFR was the most frequently mutated cancer gene in MIA, AIS, and IAC (9). Our founding also indicated that there was a high discrepancy of driver mutations in NSCLC patients with ground-glass nodules (GGNs) (4,38). EGFR mutation status including L858R mutation and 19 deletions, KRAS mutations or ALK rearrangements occurred frequently in patients with GGO (34).…”
Section: Discussionsupporting
confidence: 78%
“…To evaluate pulmonary GGO and investigate the correlation between CT imaging features and LUAD driver genes or subtypes is helpful for diagnosis and clinical management. Pleural retraction, GGO proportion, and margin signature should be focused initial evaluation of histological subtypes in early stage LUADs (4). Different studies have different definition of GGO proportion and the following parameters have been used to calculate the GGO proportion: area ratio of tumor on mediastinal windows to that on lung windows, consolidation/tumor dimension ratio, GGO/tumor area ratio, the product of the dimension ratio of the tumor on mediastinal windows and GGO/ tumor volume ratio (33) to calculate the tumor shadow disappearance rate (TDR) (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this new classification, adenocarcinomas were classified as atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma with lepidic, acinar, papillary, micropapillary or solid growth patterns (7). The presence of invasive components, especially with a solid or micropapillary growth pattern, correlated with poor prognosis in lung cancers (8,9). On CT scans, less aggressive subtypes such as AIS, MIA and lepidic adenocarcinomas frequently present as pure GGN (9).…”
Section: Original Articlementioning
confidence: 99%
“…The presence of invasive components, especially with a solid or micropapillary growth pattern, correlated with poor prognosis in lung cancers (8,9). On CT scans, less aggressive subtypes such as AIS, MIA and lepidic adenocarcinomas frequently present as pure GGN (9). While the presence of aggressive subtypes, such as solid and micropapillary growth patterns, greatly impacts the disease recurrence and overall survival for patients with GGN (10,11).…”
Section: Original Articlementioning
confidence: 99%